Evaluation of Parathyroidectomy for Secondary and Tertiary Hyperparathyroidism by the Parathyroid Surgeons’ Society of Japan - Yoshihiro Tominaga; Takatoshi Kakuta; Chikao Yasunaga; Michio Nakamura; Yoshiyuki Kadokura; Hideki Tahara (2016)
Abstract Secondary hyperparathyroidism (SHPT) remains a serious complication in patients with chronic kidney disease, and some patients require parathyroidectomy. The Parathyroid Surgeons’ Society of Japan (PSSJ) evaluated parathyroidectomy for SHPT and tertiary hyperparathyroidism (THPT) in Japan. The annual numbers of parathyroidectomies between 2004 and 2013 were evaluated using questionnaires. Since 2010, the PSSJ has registered the patients. In total, 826 patients from 42 institutions were registered. The annual number of parathyroidectomies for SHPT and THPT in Japan increased from 2004 to 2007 and then decreased markedly after 2007, with 296 operations performed in 2013. The number of women and men was almost equal (397/427). Median (interquartile range) age of these patients was 59.0 (24–87) years, the duration of hemodialysis before parathyroidectomy was 10.83 (0.0–38.7) years, and diabetic nephropathy was 87/826 (10.5%). Of these patients 59.6% were treated with cinacalcet at undergoing parathyroidectomy. In 75.3% of patients, a total parathyroidectomy with forearm autograft was performed. In 77.7% of patients, four or more parathyroid glands were removed during the initial operation. The incidences of husky voice and wound hemorrhage were 2.9% and 1.1%, respectively. The number of parathyroidectomies for SHPT in Japan decreased markedly after the introduction of cinacalcet. Based on the evaluation of registered patients, parathyroidectomies have been successfully performed at the institutions participating in the PSSJ.